Etika Belaian Sebagai Sebuah Model Etika Pasca-Modern - Hendar Putranto (Respons: Jurnal Etika Sosial, 2008)
Post-modernism offers new and unprecedented challenges in the light of morality issues. Some of the big issues faced by post-modern way is how to respond to ambivalence and how to treat “the Other” in a more fair and dignified way. Here, these issues are “answered” by post-modern ethics as articulated by Polish-British thinker, Zygmunt Bauman. Arguably, the role-model of post-modern ethics is an ethic of care since it highlights and prioritizes the act of care and responsibility toward others in a (more) flexible way while at the same time recognizing the differences. Nevertheless, an ethics of care is a sufficient but not necessary response to the moral issues of our times because of some inherent flaws.